Blended learning: making an impact on assessment and self‐reflection in accounting education. Issue 2 (2014) - ,; ,; ,
Abstract : Purpose – The purpose of this paper is to describe the evolution of a blended learning strategy in a company law course for accounting students and to evaluate its impact on assessment and student self‐reflection.Design/methodology/approach – A case study approach is used to describe the development of blended learning technologies within an elevator pitch assessment item in four cohorts over a two‐year period. This is complemented by teacher observations, an online survey and student interviews to evaluate the assessment item, the technology used and its impact as a self‐reflection and assessment tool.Findings – The case study reveals the benefits of blended learning technologies but also a series of logistical, assessment‐related, behavioural and technological issues and how these issues were addressed. The preliminary evidence from the online survey and student interviews suggests that the blended learning technologies have facilitated flexibility in assessment (both from a student and teacher perspective), student self‐reflection and fairness in assessment practices.Originality/value – The study identifies the benefits of and likely issues facing educators when considering the deployment of blended learning technologies to teach and assess oral communication skills. The paper contributes to pedagogy by describing the innovative use of video cameras in assessing elevator pitches and extends the literature on video presentations in higher education, in particular, its positive influence on student self‐reflection.